The Australian Burroughs courier - Tompkins, Allan J. (Allan James) (Melbourne, Victoria : Allan J. Tompkins, 1970)
An amateur magazine published for readers, students and collectors of the works of Edgar Rice Burroughs.
Caption title.
Edgar Rice Burroughs (September 1, 1875-March 19, 1950) was an American writer best known for his creations of the jungle hero Tarzan and the heroic Mars adventurer John Carter, although he produced works in many genres.
Keywords: Burroughs, Edgar Rice, -- 1875-1950 -- Periodicals; Fantasy fiction -- Appreciation -- United States -- Periodicals; Science fiction -- Appreciation -- United States -- Periodicals; Authors, American -- Periodicals; Australian; Fan magazines